Z′ Portal Dark Matter in the Minimal B-L Model - Satomi Okada (Advances in High Energy Physics)
We consider a dark matter scenario in the context of the minimal extension of the Standard Model (SM) with a B-L (baryon number minus lepton number) gauge symmetry, where three right-handed neutrinos with a B-L charge -1 and a B-L Higgs field with a B-L charge +2 are introduced to make the model anomaly-free and to break the B-L gauge symmetry, respectively. The B-L gauge symmetry breaking generates Majorana masses for the right-handed neutrinos. We introduce a Z2 symmetry to the model and assign an odd parity only for one right-handed neutrino, and hence the Z2-odd right-handed neutrino is stable and the unique dark matter candidate in the model. The so-called minimal seesaw works with the other two right-handed neutrinos and reproduces the current neutrino oscillation data. We consider the case that the dark matter particle communicates with the SM particles through the B-L gauge boson (ZB-L′ boson) and obtain a lower bound on the B-L gauge coupling (αB-L) as a function of the ZB-L′ boson mass (mZ′) from the observed dark matter relic density. On the other hand, we interpret the recent LHC Run-2 results on the search for a Z′ boson resonance to an upper bound on αB-L as a function of mZ′. These two constraints are complementary for narrowing down an allowed parameter region for this “Z′ portal” dark matter scenario, leading to a lower mass bound of mZ′≥3.9 TeV.